2015
DOI: 10.1111/eci.12456
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of normal TSH value among patients with autonomously functioning thyroid nodule

Abstract: Background International guidelines significantly diverge on the effectiveness of thyroid scintigraphy (TS) in the initial work-up of thyroid nodules. In particular, the role of TS to detect or exclude the presence of autonomously functioning thyroid nodules (AFTN) in patients with normal serum thyrotropin (TSH) is still a matter to debate. Here, we aimed to review the literature on the prevalence of normal TSH value among patients with AFTN and meta-analyse data of the retrieved eligible papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 34 publications
(65 reference statements)
3
39
0
6
Order By: Relevance
“…If the 99m Tc thyroid scan identifies a cold nodule, the patient will undergo thyroid FNA, while if the 99m Tc thyroid scan identifies a hot nodule, the patient will not undergo FNA. This approach is largely approved in the literature [18][19][20][21][22][23][24] and is justified by the fact that most functional thyroid nodules are follicular adenomas and hyperplasia, and in these cases FNA is often not conclusive. This could be used as a first tool to reduce the number of FNAs with a TIR-3 diagnosis, which is the most controversial and clinically complex FNA category.…”
Section: Discussionmentioning
confidence: 99%
“…If the 99m Tc thyroid scan identifies a cold nodule, the patient will undergo thyroid FNA, while if the 99m Tc thyroid scan identifies a hot nodule, the patient will not undergo FNA. This approach is largely approved in the literature [18][19][20][21][22][23][24] and is justified by the fact that most functional thyroid nodules are follicular adenomas and hyperplasia, and in these cases FNA is often not conclusive. This could be used as a first tool to reduce the number of FNAs with a TIR-3 diagnosis, which is the most controversial and clinically complex FNA category.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were evaluated by US, while additional imaging including whole body scintigraphy, magnetic resonance imaging, computed tomography, and positron emission tomography/computed tomography was used when needed. This approach was based on our previous experience spanning more than a decade and is also supported by the most recent literature …”
Section: Methodsmentioning
confidence: 98%
“…Furthermore, the EANM believes that thyroid scintigraphy still has its place in the diagnostic workup of nodular thyroid disease, especially in regions, including a number of EANM member countries, with a known or recently alleviated iodine deficiency. In such populations a normal TSH level cannot rule out thyroid autonomy [8][9][10][11]. In their retrospective study, Chami et al [9] found that 49 % of patients with an autonomously functioning focal thyroid nodule had a normal TSH level.…”
mentioning
confidence: 99%